2016
DOI: 10.3390/md14100181
|View full text |Cite
|
Sign up to set email alerts
|

New Metabolites and Bioactive Actinomycins from Marine-Derived Streptomyces sp. ZZ338

Abstract: An extract prepared from the culture of a marine-derived actinomycete Streptomyces sp. ZZ338 was found to have significant antimicrobial and antiproliferative activities. A chemical investigation of this active extract resulted in the isolation of three known bioactive actinomycins (1–3) and two new metabolites (4 and 5). The structures of the isolated compounds were identified as actinomycins D (1), V (2), X0β (3), 2-acetylamino-3-hydroxyl-4-methyl-benzoic acid methyl ester (4), and N-1S-(4-methylaminophenylm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…Our previous studies 23 , 27 , 28 proposed that the in vitro SRB screening assay combined with the detection of lactate production might be a new way to discover novel anti-glioma compounds from marine actinomycetes with unique mechanism by regulating multiple tumor metabolic enzymes. The data from this study further support this proposal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies 23 , 27 , 28 proposed that the in vitro SRB screening assay combined with the detection of lactate production might be a new way to discover novel anti-glioma compounds from marine actinomycetes with unique mechanism by regulating multiple tumor metabolic enzymes. The data from this study further support this proposal.…”
Section: Resultsmentioning
confidence: 99%
“…Each extract prepared from the cultures of the isolate marine bacteria was assayed by sulforhodamine B (SRB) method for its activities in inhibiting the proliferation of glioma cells and in reducing the production of lactate in glioma cells. It has been found that several extracts had antiproliferative activity and also reduced lactate production in glioma cells, resulting in the discovery of several anti-glioma compounds by downregulating multiple tumor glycolytic enzymes 23 , 27 , 28 . These results suggested that the in vitro antiproliferative active assay in combination with the determination of lactate production might be a new method to discover novel anti-glioma agents with the unique mechanism of targeting multiple tumor metabolic regulators.…”
Section: Introductionmentioning
confidence: 99%
“…They are a family of bicyclic chromopeptide lactones that attach two pentapeptide lactones of nonribosomal origin. Its use dates approximately 70 years ago, acting under several types of malignant human tumours, including nephroblastoma (Wilms’ tumour) and childhood rhabdomyosarcoma 67 69 , and has attracted attention for its potential to assist in the development growth of multi-drug resistance strains and inhibition of HIV-1 reverse transcriptase 44 , 70 , 71 .…”
Section: Discussionmentioning
confidence: 99%
“…Actinomycin V (Act V), which is also extracted from the marine-derived actinomycete Streptomyces sp. [ 1 ], has a similar structure to that of Act D ( Figure 1 ). In our previous studies [ 10 , 11 ], Act V was found to be more cytotoxic to tumor cells than Act D. Moreover, Act V inhibited the migration and metastasis of breast cancer cells.…”
Section: Introductionmentioning
confidence: 94%
“…Actinomycin D (Act D), extracted and separated from the marine-derived actinomycete Streptomyces sp . [ 1 ], is a chemotherapy medication that inhibits RNA synthesis [ 2 ]. It has been used for the treatment of multiple cancer types, including Wilms tumor [ 3 ], rhabdomyosarcoma [ 4 ], Ewing’s sarcoma [ 5 ], trophoblastic neoplasms [ 6 ] and certain types of ovarian cancer [ 7 ].…”
Section: Introductionmentioning
confidence: 99%